Tuberculosis Regional Training and Medical Consultation Centers in the United States: Characteristics, outcomes, and quality of medical consultations, June 1, 2010 — May 31, 2014 - Mase, Sundari R.; Samron, Ratima; Ashkin, David; Castro, Kenneth G.; Ryan, Stephen; Seaworth, Barbara; Chen, Lisa; Lardizabal, Alfred; Tuckey, Dawn; Khan, Amera; Posey, Drew L.; Chappelle, Courtney; et al. (Journal of clinical tuberculosis and other mycobacterial diseases, 2019)
Tuberculosis (TB) Regional Training and Medical Consultation Centers (RTMCCs) were established in 2005 for TB medical consultation, training and education in the United States. A medical consultation database (MCD) captured all consultations provided by RTMCCs; we report on those provided from June 1, 2010 to May 31, 2014. All MCD consultations during 2010–2014 were categorized into: provider type, setting, consultation topic, and patient age. We analyzed data frequencies and performed subgroup analyses by RTMCC, by TB incidence for the geographical area, and by year of consultation. End-user satisfaction was assessed by a 2016 telephone evaluation of RTMCC services. A total of 11,074 consultations were delivered, with 10,754 (97.1%) in the U.S. and its current or former territories. Of these, 6018 (56%) were for high, 2443 (22.7%) for medium, and 2293 (21.3%) for low TB incidence settings. Most were for adults (81.3%) and answered within 24 h (96.2%). Nearly 2/3 consultations originated from health departments; providers included mostly physicians (44.3%) or nurses (37.6%). Common consult categories included TB disease (47.7%), case management (29.8%), latent TB infection (19.3%), diagnosis (16.1%), pharmacology (14.7%) and adverse side effects (14.3%). Among adverse side effects, hepatotoxicity was most common (39.6%). Volume and nature of consult requests remained relatively stable over the four-year period. Feedback from a 2016 CDC evaluation indicated overall satisfaction with RTMCC medical consultation services. RTMCCS were an important source of TB medical consultation over the time-frame of this assessment and provided quality expert consultation within 24 h. RMTCCs represent a reservoir of TB subject-matter expertise in the United States.